Afamin predicts gestational diabetes in polycystic ovary syndrome patients preconceptionally. Issue 5 (May 2019) - Köninger, Angela; Iannaccone, Antonella; Hajder, Ensar; Frank, Mirjam; Schmidt, Boerge; Schleussner, Ekkehard; Kimmig, Rainer; Gellhaus, Alexandra; Dieplinger, Hans
Abstract : Background: Patients suffering from polycystic ovary syndrome (PCOS) are often insulin resistant and at elevated risk for developing gestational diabetes mellitus (GDM). The aim of this study was to explore afamin, which can be determined preconceptionally to indicate patients who will subsequently develop GDM. Serum concentrations of afamin are altered in conditions of oxidative stress like insulin resistance (IR) and correlate with the gold standard of IR determination, the HOMA index. Methods: Afamin serum concentrations and the HOMA index were analyzed post hoc in 63 PCOS patients with live births. Patients were treated at Essen University Hospital, Germany, between 2009 and 2018. Mann–Whitney U test, T test, Spearman's correlation, linear regression models and receiver-operating characteristic (ROC) analyses were performed for statistical analysis. Results: Patients who developed GDM showed significantly higher HOMA and serum afamin values before their pregnancy ( P < 0.001, respectively). ROCs for afamin concentrations showed an area under the curve of 0.78 (95% confidence interval (CI) 0.65–0.90) and of 0.77 (95% CI 0.64–0.89) for the HOMA index. An afamin threshold of 88.6 mg/L distinguished between women who will develop GDM and those who will not with a sensitivity of 79.3% and a specificity of 79.4%. A HOMA index of 2.5 showed a sensitivity of 65.5% and a specificity of 88.2%. Conclusion: The HOMA index and its surrogate parameter afamin are able to identify pre-pregnant PCOS patients who are at risk to develop GDM. Serum afamin concentrations are independent of fasting status and therefore an easily determinable biomarker.